Molecular Subtypes Of Breast Cancer An Immunohistochemistry Study In Iraqi Women - Ghalib, Asma; Abid, Shayma Ghalib (Medical Science Journal for Advance Research, 2024)
Background: Breast tumors are a familiar type of tumor that the factors affecting womenfolk were diverse and had a variety of histological manifestations. Historically, <breast tumor> studies tended to lump all cases together, but there is now a widespread acknowledgment that identification of <breast tumor> encompasses various subatomic subclasses of disease. The current histological categorizations <breast tumor> lack precision when it comes to accurately predicting a patient's prognosis. Tumors that appear identical under microscopic examination can exhibit varying clinical outcomes. The primary cause of this can be mainly attributed to variations in molecular categorizing among the histologically similar types. Objective: Molecular categorizing <breast tumor> in Iraqi women, Using <Digimizer software> for image analysis of immunohistochemical expression of these factors. Materials and methods: This is a retrospective and prospective study involving 64 females cases with breast tumor their age ranged from 21 years old to 67 years old were included in this study. They were attendants of Al –Kadhimiyia the teaching hospital and Medicine city the teaching hospital in Baghdad and from private laboratory in Baghdad in the period between 2010 to 2011. The diagnosis in each case was established by clinical diagnosis and confirmed by histopathological diagnosis. All of the patients were newly diagnosed not receiving neither radiotherapy nor chemotherapy treatment preoperatively. By using Immunohistochimistry (IHC) to evaluate the expression of ER, PR, HER2/neu, HER1 (EGFR) and CK5/6 markers for subatomic classification. Results: The luminal type was the most common subtype in breast tumor (80%), which was followed by the basal subtype (9%). HER2 subtype were 8% from the total of cases, and 3% unclassified subtype. The largest rate of high-grade cases was linked to HER2. Basal type is displayed aggressive features, such as large tumor size, lymph nodes involvement and poorly differentiated cancers. Luminal A included the highest percentage of patients, the highest proportion of stage I–II tumors and well/moderately differentiated lesions. HER2-type was more frequent in invasive ductal carcinoma and showed a high percentage of positive lymph nodes. Conclusions: The clinical features have been found to have a strong correlation with these subatomic differences, and in some cases, they have proven to be even more reliable than traditional histopathological parameters. By uncovering specific molecular characteristics Cancer of the breast, we have gained a deeper understanding of the disease's pathophysiology and have been able to devise more targeted therapeutic approaches.